Forests, illegality, and livelihoods: the Case of Cameroon - Cerutti, P.O.; Tacconi, L. (Informa UK Limited, 2008)
Concern about illegal logging has grown considerably over the past decade. This article contributes to knowledge on the nature, extent, and impacts of illegal logging (IL), with particular focus on livelihoods. We find that the reality of IL is much more nuanced than it has been depicted. We show that the illegal log harvest in Cameroon is smaller than previously thought and that in recent years small-scale operators, forced to operate illegally by an illicit ministerial decision, contributed a significant share of the illegal harvest. We also show the role played by the state in IL. We derive priority areas for interventions that address IL and its impacts.